ANALISIS MOTIVASI MENABUNG IBU RUMAH TANGGA DI KELURAHAN KEBONSARI KECAMATAN SUMBERSARI KABUPATEN JEMBER - Oktarina Dian Siska; Sutrisno Djaja (Economic Education, University of Jember, 2015)
Saving motivation is a self-boosting to undertake an activity to spare fund which is useful in the future. This research aimed to analyze housewives’ saving motivation and to analyze the allocation of the use of houseife’s savings in administrative village of Kebonsari, District of Sumbersari, Jember Regency.The research location was determined using purposive method, that is, administrative village of Kebonsari, District of Sumbersari, Jember Regency. Data were collected by document search, interviews and observation. Data analysis involved data reduction, data presentation and then conclusion drawing. Based on data on the field, it was found that housewives’ saving motivations in administrative village of Kebonsari were setting goals of saving, determining the allocation of saving time, saving budget by a certain time and being persistent. Saving motivations which were rarely set by housewives were making expenditure records and reconsidering of money saving. Furthermore, the saving motivations that were never set by housewives were cutting spendings, considering priority, and terminating the use of creditn cards. The savings allocations made by housewives were for tuition, disaster anticipation, unemployment or retirement anticipation, the cost of repairing or buying household appliances and funds for celebration of important religious holidays and weddings. Sources of fund saving were in the form of cash saved on the passbook at financial institutions of bank and non-bank